Elevated free triiodothyronine may lead to female sexual dysfunction in Chinese urban women: A hospital-based survey - Han Luo (Nature Portfolio, 2017)
Abstract Research on female sexual dysfunction (FSD) is limited, especially in China, due to conservative culture and beliefs. There has been a dearth of FSD screening research in China since the optimal cutoff value of the Chinese version of the Female Sexual Function Index (CVFSFI) was determined in 2014. At the same time, the relationship between thyroid hormones and FSD has seldom been explored in Chinese women. Therefore, hospital-based research was conducted to elucidate FSD frequency and risk factors. Women who underwent a check-up at the Health Promotion Center were approached to participate and, if consented, were enrolled in the study. Demographic and socioeconomic data was extracted. All participants completed the CVFSFI and Beck Depression Inventory (BDI) self-report questionnaires and underwent thyroid hormone tests. A total of 1119 participants were included in the final analysis, with a mean age of 38.6 ± 7.6 years and average CVFSFI score of 25.7 ± 3.9. The frequency of FSD among the participants in this hospital-based cross-sectional study was 26.5%. In addition to age, menopause, parity and depression status as risk factor, and annual income (40,000–100,000 RMB/year) and educational background (≥university) as protective factor, elevated free triiodothyronine (fT3) was identified as an independent risk factor of FSD.